2017
DOI: 10.1080/13527266.2017.1392337
|View full text |Cite
|
Sign up to set email alerts
|

Exciting on Facebook or competent in the newspaper? Media effects on consumers’ perceptions of brands in the fashion category

Abstract: Media investments are continuously shifting from traditional media like newspapers to digital alternatives like websites and social media. This study investigated if and how media choice between the two rival channels can influence consumers' perceptions of a novel brand. 504 Swedish retail fashion customers participated in an experiment to evaluate the identical advertisement placed either in a national newspaper or on Facebook. The results revealed that advertising in a newspaper can have a positive effect o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…Through the analysis of digital user‐generated content, some studies have provided evidence that consumers naturally use human personality characteristics and traits to refer to brands (Paschen et al., 2017; Ranfagni et al., 2016). By applying the premises and models of BP theory to digital settings, other studies have further confirmed that BP perceptions positively affect consumer responses, such as customer satisfaction (Ong et al., 2017), brand attitude (Torres & Augusto, 2019), and brand equity (Anselmsson & Tunca, 2019).…”
Section: Review Findings (Tccm)mentioning
confidence: 91%
See 2 more Smart Citations
“…Through the analysis of digital user‐generated content, some studies have provided evidence that consumers naturally use human personality characteristics and traits to refer to brands (Paschen et al., 2017; Ranfagni et al., 2016). By applying the premises and models of BP theory to digital settings, other studies have further confirmed that BP perceptions positively affect consumer responses, such as customer satisfaction (Ong et al., 2017), brand attitude (Torres & Augusto, 2019), and brand equity (Anselmsson & Tunca, 2019).…”
Section: Review Findings (Tccm)mentioning
confidence: 91%
“…Apart from the lack of variety of digital touchpoints, the in‐depth analysis of digital contexts further shows that research has mainly been conducted in a single digital context (e.g., Chang, 2012). Only eight articles (see Table 3) examined consumers’ BP perceptions at different types of digital touchpoints, for example, across websites and social media platforms (e.g., Eigenraam et al., 2021; Ranfagni et al., 2016), or compared consumers’ BP perceptions that were drawn from an online context with those from an offline context (e.g., Anselmsson & Tunca, 2019; Chan et al., 2018). By contrast, the vast majority of studies opted to choose one digital touchpoint as representative for the digital environment (e.g., Ong et al., 2017).…”
Section: Review Findings (Tccm)mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, consumer reviews on social media are forcing fashion retailers to produce the products the market wants now. In fact, recent research found that Facebook, a social media platform, influences purchasing intentions through perceptions of the brand as being exciting (Anselmsson and Tunca, 2019). Moreover, influencers , those virtual stars with many virtual followers, are driving fashion retailers to stock the products they recommend in real time.…”
Section: High Velocity Environments: the Korean Fashion Industrymentioning
confidence: 99%
“…Online word of mouth recommendations have been evidenced by previous research (e.g., Roy, Datta, and Mukherjee 2019) to have a strong influence on purchase intentions, hence actual buys. Also, favourable user-generated content on social media contributes positively to brand equity and brand attitude (Schivinski and Dabrowski 2016), especially in the fashion industry where the choice of social media channels for marketing communications would be highly critical (Anselmsson and Tunca 2019). Therefore, targeting younger generations who are tech-native can be more effective if fashion brands supplement the content shared with a proper blend of entertaining elements like music, games, riddles, etc., which are already doable given the fast-growing set of rich-media features within the Instagram environment.…”
Section: Practical Implicationsmentioning
confidence: 99%